Analisis Kearifan Lokal Kampung Adat Tamkesi Sebagai Daya Tarik Wisata Di Kabupaten Timor Tengah Utara Nusa Tenggara - Kusmayadi; Adrianus Lopo Anunut (Jurnal Sains Terapan Pariwisata, 2016)
Basically tamkesi community , in the district of north central timor is one of a small community of nations or atoni meto dawan , that is still trying to defend and preserve cultural values a legacy received from their fathers .This can be evidenced by material objects and cultural relics non material such as the customary ritual ceremonies still be implemented as of his supporters . Such local wisdom tough, who can be saved reconstructed, and rehab will be part of the community in an effort to build tamkesi cultures and customs. Their tamkesi is customary order to hold tightly cultures and customs and still preserving cultural heritage, the local until now. The form of local wisdom is customary ceremonies and keep that belief systems are still in tamkesi by the community. Means of living in traditional local wisdom , so that culture and customs that can not in split with each other. If the community customs but not only run balanced with the knowledge of local culture and it will be limping local wisdom.